Hubungan Social Capital dengan Pengembangan Usaha Tani Hortikultura Anggota Kelompok Petani Muda di Desa Berjo, Ngargoyoso, Karanganyar - Afifah Ayu Nur Aini; Suwarto Suwarto; Emi Widiyanti (AGRITEXTS: Journal of Agricultural Extension, 2024)
The development of farming business is inseparable from the existence of effective and efficient farm business management. Farm business management is the ability of farmers to plan, organize, direct, coordinate and supervise the factors of production that are controlled or owned so that they can provide production as expected. The success of farming in the agricultural sector is undeniably largely determined by social capital. This study aims to determine the characteristics of social capital among members of the young farmer group, knowing the development of horticultural businesses contained in members of the young farmer group and analyzing the relationship between social capital and the business development of members of the young farmer group. This research uses quantitative methods. This research was supervised and funded by Merdeka Belajar-Kampus Merdeka (MBKM)/Independent Learning-Independent Campus Research, which is located in Berjo Village, Ngargoyoso, Karanganyar. The regional election was carried out deliberately based on information obtained by research supporting data that showed that there were 2 groups of young farmers who had been active in business development in the agricultural sector since 2019. The sampling technique used was a saturated sampling of 27 young farmers. The results showed that cooperation and participation have a significant relationship with business development. Meanwhile, trust and networks have no significant relationship with the development of farming businesses.